Cardiomyocyte-Specific JunD Overexpression Increases Infarct Size following Ischemia/Reperfusion Cardiac Injury by Downregulating Sirt3 - Akhmedov, Alexander; Montecucco, Fabrizio; Costantino, Sarah; Vdovenko, Daria; Schaub Clerigué, Ariane; Gaul, Daniel S.; Burger, Fabienne; Roth, Aline; Carbone, Federico; Liberale, Luca; Amrollahi-Sharifabadi, Mohammad; Vellone, Valerio Gaetano; Eriksson, Urs; Matter, Christian M.; Crowe, Lindsey A.; Vallée, Jean-Paul; Paneni, Francesco; Vanhoutte, Paul M.; Camici, Giovanni G.; Mach, François; Lüscher, Thomas F. (Thrombosis and Haemostasis, 2020)
Ischemia/reperfusion (I/R) injury in acute myocardial infarction activates several deleterious molecular mechanisms. The transcription factor JunD regulates pathways involved in oxidative stress as well as in cellular proliferation, differentiation, and death. The present study investigated the potential role of JunD as a modulator of myocardial injury pathways in a mouse model of cardiac I/R injury. Infarct size, systemic and local inflammation, and production of reactive oxygen species, as well as cytosolic and mitochondrial apoptotic pathways were investigated in adult males after myocardial I/R. In wild-type (WT) mice, 30 minutes after ischemia and up to 24 hours following reperfusion, cardiac JunD messenger ribonucleic acid expression was reduced while JunB increased. Cardiac-specific JunD overexpressing mice (JunDTg/0) displayed larger infarcts compared with WT. However, postischemic inflammatory or oxidative responses did not differ. JunD overexpression reduced Sirt3 transcription by binding to its promoter, thus leading to mitochondrial dysfunction, myocardial cell death, and increased infarct size. On the other hand, JunD silencing reduced, while Sirt3 silencing increased infarct size. In human myocardial autopsy specimens, JunD-positive areas within the infarcted left ventricle staining corresponded to undetectable Sirt3 areas in consecutive sections of the same heart. Cardiac-specific JunD overexpression increases myocardial infarct size following I/R. These effects are mediated via Sirt3 transcriptional repression, mitochondrial swelling, and increased apoptosis, suggesting that JunD is a key regulator of myocardial I/R injury. The present data set the stage for further investigation of the potential role of Sirt3 activation as a novel target for the treatment of acute myocardial infarction.
Keywords: transcription factor; myocardial infarction; ischemia and reperfusion